Design and fabrication of an innovative 360 degree standing fan / Muhammad Hazeq Misuan - Misuan, Muhammad Hazeq (2022)
Fan is one of the significant engineering applications that has contribute to mankind in many ways. For example, oscillating fans are widely used in our life to aid air circulation throughout the surrounding. However, a standard standing fan moves back and forth and only throws air in a limited front area due to its oscillating mechanism. Due to this problem, many people are forced to spend and waste their money to buy another extra fan and place it side by side just to provide comfortable cool air from both fans for a whole space. Hence, to solve this problem, the project creates a standing fan that can rotate 360 degrees horizontally and is named as design and fabrication of an innovative 360-degree standing fan. The two main objectives of this product are to offer a fan that provides comfort in everyday life by ensuring the air from the fan can be supplied in all directions and to fabricate and design the product successfully. In order to fabricate this product, several methodologies have been used such as computational analysis and fabrication process. As a result, this product successfully rotates 360 degrees horizontally thus can be placed in the centre of the room or the area in order to deliver the air to the fullest potential. However, it is undeniable that there are advantages and limitations to this product. Despite the limitations, the objectives of the project are successfully achieved hence the 360-degree standing fan can produce cool and breeze air throughout the surrounding in all directions.